Ekstraksi Dan Karakterisasi Pektin Kulit Jeruk Manis Kisar (Citrus sp.) - Latupeirissa, Jolantje; Fransina, Eirene G.; Tanasale, Matheis F.J.D.P. (Jurusan Kimia, Fakultas Sains dan Teknologi, Universitas Pattimura, 2019)
Extraction and characterization of pectin from the oranges peel of kisar (Citrus sp.) have been done. Pectin was obtained from extraction oranges peel crust of kisar with HCl at temperature 90 °C during 4 hours. The content of albido and pectin are 69.17% and 82.82%, respectively. Identification functional group of pectin was using by FTIR spectrophotometer which OH-alcohol (3294.42–3373.50 cm-1), CH3-alifatic (2939.52 cm-1), C=O ester (1741.72–1730.15 cm-1), C=C alkene (1614.42–1643.35 cm-1), and C-O eter (1232.51–1276.88 cm-1). Characterizations of pectin were equivalent weight (2011.6 mg), methoxyl content (1.17%), galacturonic level (41.64%), moisture content (28.46%), ash content (11.92%), and degree of esterification (15.95%).